The presence of invasive grasses affects the soil seed bank composition and dynamics of both invaded and non-invaded areas of open savannas - Dairel, Mariana [UNESP]; Fidelis, Alessandra [UNESP] (Elsevier, 2020)
One of the major threats to tropical savannas globally is the invasion by alien grasses. In systems frequently disturbed, individuals can be recruited from the seed bank, and areas under natural regeneration can be more easily invaded when exotic newcomers are in the system, including the presence of invasive propagules in the soil seed bank. This study analyzed the dynamics of the soil seed bank in invaded and non-invaded areas of open savannas elucidating the potential of grass regeneration from the seed bank. Soil samples were collected in areas with different invasive grasses: Urochloa brizantha (Hochst. ex A. Rich.) R.D.Webster – synonym Brachiaria brizantha (Hochst. ex A. Rich.) Stapf, Melinis minutiflora Beauv. and areas with native vegetation. Soil seed bank was assessed using two techniques: seed counting and seedling emergence. Dominant species in each area influenced the seed bank composition, showing the highest densities from April to September. In invaded areas, the seed bank was composed mainly of invasive grasses that contributed to 98% (670 ± 382 seeds.m−2) of total seeds. In non-invaded areas, the soil seed bank presented the highest density (65%, 135 ± 38 seeds.m−2) of native species. However, the presence of invasive grasses was significant, with 35% of the total seeds belonging to U. brizantha. Although non-invaded areas have a higher potential for regeneration by native grasses, the presence of invasive grasses in the seed bank is an indication that the invasive species is already in the system and changes in the aboveground cover could accelerate the invasion process. Early management efforts towards establishing and/or established invasive species before seed dispersal could help reduce the soil seed bank load and should be carried out to control and avoid the establishment of African grasses, since they can dominate the seed bank in non-invaded areas if they are present in neighboring areas, affecting the dynamics of plant communities.
Keywords: African invasive species; Germination; Grasses; Natural regeneration; Regeneration niche